Surveying the spatiotemporal changes of afforestation in the Nyírség – from the aspect of wind erosion - Négyesi, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2018)
The aim of our study was to carry out a detailed survey on the spatiotemporal changes of afforestations (forests and shelterbelts) in the Nyírség. The base data for mapping the changes of forests and shelterbelts consisted of the maps of I, II and III Military Surveys of Hungary from the 1940’s, civil topographic maps from the 1980’s and ortophotographs from 2005. Besides these data sources, CORINE Land Cover database from 2000, 2006, 2012 and a forest database containing the species distribution of forests from 2014 were also used for surveying the changes of forest cover. Our results pointed out that large differences were found in forest cover and in the length of shelterbelt systems as well as in the tendency of changes in different parts of the Nyírség. On the one hand all the forests and shelterbelts are situated on the two sides of the Nyírség watershed: the dominance of shelterbelts on the northern side and forests on the southern side can be observed in relation with soil properties. Nevertheless, the increase of forest area is continuous but the length of shelterbelts has decreased since the change of regime. In connection with wind shelterbelts we can conclude that half-two- thirds part of the shelterbelts are planted improperly in the two study area (Western Nyírség, Southern Nyírség). It can be explained by the high rate of one-row shelterbelts, the discontinuity of shelterbelts and the improper direction of planting.